Faktor Yang Mempengaruhi Calon Mahasiswa Dalam Memilih Perguruan Tinggi Di Provinsi Lampung - Yan Aditiya Pratama; Stefanus Rumangkit; Abdi Darmawan; Ade Mousadecq (Jurnal Humanipreneur, 2023)
This type of research is case study research. The data used in this study are primary data. The population is high school students in Lampung province. The sampling technique uses probability sampling techniques, namely Proportionate Stratified Random Sampling using the Slovin formula. Proportionate Stratified Random Sampling is a sampling technique when a population has heterogeneous members or elements and is proportionally stratified. Therefore, the sampling to be taken is high school / vocational students grade 1, 2, and 3 in this study. Furthermore, the measurement of variables in the study used the Semantic Differential Scale with factors of interest, motivation, parental background, expected work, and learning environment as variables.